Material Model of the AlCu2SiMn Alloy Under Hot Plastic Forming - Gontarz, A.; Pater, Z. (Engineering Transactions, 1999)
The results of the torsion tests investigation of AlCu_2MnSi aluminium alloy are presented in this paper. The experiments were carried out at the temperature range between 350°C and 500°C and at a twist rate of 8.3 rpm, 750 rpm and 1500 rpm. Various ways of interpretation of the torsion test were shown. A comparison between the results of torsion and compression tests was done, as well. Using the results of this comparison, the Tresca hypothesis was chosen for the calculation of both the flow stress and of the equivalent strain. The flow curves and the limit strain curves were obtained for investigated conditions. Moreover, the range of hot forming temperatures of the analysed alloy was estimated. The obtained results were used for constructing the material model of AlCu_2SiMn alloy. This model was used for the numerical simulation of the cross-wedge rolling process [7].